The Influence of Products, Promotions And Discounts On Car Purchase Decisions at PT. Kumala Brilliant Immortal Wuling Motors Parepare City - Pandi Putra; Ulyana Muslimin (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2023)
The Influence of Products, Promotions and Discounts on Car Purchase Decisions at PT. Kumala Brilliant Immortal Wuling Motors Parepare City This study aims to determine how much influence the quality of the product, promotions and discounts on the decision to buy a car at PT. Kumala Brilliant Immortal Wuling Motors Parepare City. The method of analysis used in this research is the method of observation, interviews, questionnaires, and documentation as well as the method of determining the sample using the Roscoe approach and obtaining 40 respondents. The analytical method used is Multiple Linear Analysis. The results of this study indicate the influence of products, promotions and price discounts simultaneously on car buying decisions at PT. Kumala Brilliant Immortal Wuling Motors Parepare City. This is evidenced by the statistical results of Fcount of 99.778 with a significance of 0.000. Because the significance value is less than 0.05 (0.000 < 0.05), this study succeeded in proving "There is an effect of Products, Promotions, and Discounts simultaneously on Purchase Decisions". The results of the R2 Determinant Test in this study obtained the value of the R2 determinant of 0.893, which means that the magnitude of the influence of Products, Promotions and Price Discounts on car buying decisions is 89.3% and the remaining 10.7 % is influenced by other variables not included in this study. Keywords : promotions, discounts, car buying decisions. Consists of one paragraph with a number of words from 150 (one hundred fifty) to 350 (three hundred fifty) words and not a summary of the article. The abstract contains a brief background of the problem and the results of the study.